IT CONSISTS OF STUDYING THE ORIGIN, BOTANICAL, AND AGROBIOLOGICAL CHARACTERISTICS OF VARIETIES OF THE SUGAR SORGHUM (SACCHARATUM) PLANT - R.O. Mirzayev (Bright Mind Publishing, 2025)
The article studies the botanical and agrobiological characteristics, growth phases, and yield indicators of the sugar sorghum (Sorgum saccharatum) plant under local conditions.
Keywords: Sakharo camel, grain sorghum, husk, dung broom, milk ripening, drought tolerant, phenological.